2005
DOI: 10.1111/j.0001-6349.2005.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Approximate entropy of fetal heart rate variability as a predictor of fetal distress in women at term pregnancy

Abstract: The ApEn of FHR variability significantly decreased during fetal asphyxia, including hypoxia, hypercapnia, and both respiratory and metabolic acidosis; low ApEn was linked to decreased power spectrum density in all frequency domains. The ApEn values may be used as a predictor of fetal distress in women at term pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Depression of HRV is associated with adverse outcomes in a number of chronic and acute pathological states, including myocardial infarction (17), congestive heart failure (3), diabetes (19), fetal asphyxia (18), and sepsis (6). In all of these conditions, the assumption has been that there is abnormal signaling from or response to the autonomic nervous system, though mechanistic studies are few.…”
mentioning
confidence: 99%
“…Depression of HRV is associated with adverse outcomes in a number of chronic and acute pathological states, including myocardial infarction (17), congestive heart failure (3), diabetes (19), fetal asphyxia (18), and sepsis (6). In all of these conditions, the assumption has been that there is abnormal signaling from or response to the autonomic nervous system, though mechanistic studies are few.…”
mentioning
confidence: 99%
“…Some studies questioned its diagnostic value (24). Recent studies in human fetuses suggested potential of FHR variability (fHRV) complexity estimation to improve clinical monitoring of fetal health (18,31). This requires a deeper understanding of the physiological meaning of fHRV complexity, including how its linear and nonlinear properties are modulated by sympathetic and vagal activity of the autonomic nervous system (ANS).…”
mentioning
confidence: 99%
“…The decreased nonlinear indices found in cases of severe MA infer fetal hypoxia, and there might be an indirect relationship between the maternal Hb content and fetal pO 2 [20]. We found that as maternal Hb increased (Figure 2), there was a trend towards increased entropy and fractal indices.…”
Section: Discussionmentioning
confidence: 56%
“…Other studies [20,37] have shown that the ApEn of FHR variability was associated not only with fetal hypoxemia, but also with respiratory and metabolic acidosis.…”
Section: Discussionmentioning
confidence: 88%